Comparative and phylogenetic analyses based on the complete chloroplast genome of Cornus subg. Syncarpea (Cornaceae) species - Guan, Bicai; Wen, Jianteng; Guo, Hanjing; Liu, Yizhen (Frontiers in Plant Science, 2024)
This study presents a comprehensive analysis of the chloroplast (cp) genomes of Cornus species, including comparative and phylogenetic evaluations, as well as examinations of their genomic structure and composition. The cp genomes exhibit a typical circular quadripartite structure and demonstrate highly similar gene order and genomic structure. The complete cp genome size of the 10 taxa in this study is 156,965 bp to 157,383 bp, where the length of the large single-copy (LSC) region is 86,296 bp to 86,691 bp, small single-copy (SSC) region is 18,386 bp to 18,454 bp, and inverted repeat (IR) region is 23,143 bp to 26,112 bp. A total of 131 genes were found, including 86 protein-coding genes (PCGs), eight rRNA genes, and 37 tRNA genes. The mean GC content of the 10 taxa is 38.145%, where the LSC region is 36.396%, the SSC region is 32.372%, and the IR region is 43.076%. Despite the relatively conserved nature of the cp genome within the species of Cornus, 25–31 simple sequence repeats (SSRs) were identified in the 10 taxa in our study. The SSRs were found to be distributed in the LSC, SSC, and IR regions in Cornus hongkongensis subsp. hongkongensis, C. hongkongensis subsp. elegans, C. hongkongensis subsp. gigantea, and C. hongkongensis subsp. tonkinensis, while the SSR was not found in the IR region of the other six taxa. Thus, whole cp genomics is a valuable tool for species identification, taxonomic clarification, and genomic evolutionary analysis. Furthermore, our findings reveal that C. hongkongensis and C. hongkongensis subsp. gigantea, along with Cornus kousa and Cornus elliptica, form sister groups. Notably, C. hongkongensis subsp. ferruginea and C. hongkongensis subsp. melanotricha did not exhibit affinity with C. hongkongensis subsp. hongkongensis. Our study furnishes essential data for further research on their classification and provides novel insights into the relationship within Cornus subg. Syncarpea.